Two Haiku for Ajay & Sheila - Bliss, Stacey (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Two Haiku dedicated to Ajay Heble and Sheila O'Reilly.